Великие русские люди: Детство и юность - Баландин Р. К. (100 великих, 2002)
Экземпляры: ( 20170714) / Инвентарный номер: 28603 / Цена: 22.22 / Сис.шифр: 63.3(2) / Авт.знак: Б20 / ГРНТИ: 03 / ББК: 63.3(2)-8